PENERAPAN STRATEGI BELAJAR PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SEKOLAH DASAR - Mukmin Mukmin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
The problem in this research is the result of a IPS class V SDN 58 Balai Makam, still low with an average valueof 67.61. The purpose of this research is to improve student learning outcomes in IPS the application of learningstrategies concept maps in the class V SDN 58 Balai Makam. This study is a class act with 2 cycles. It can beseen in student learning outcomes the average value of 67.61 increased to 70.28 in cycle I. From the first cycleto the second cycle increased by 77.52. Overall increased 14.66%. The average percentage of classicalcompleteness of student learning outcomes also increased. At the score of the first cycle of 66.66%, and thesecond cycle increased to 85.71%. So overall completeness of the classic rose 28.56%. In the teachers' activitieshas increased in each cycle. While in the first cycle the average percentage of the activity of the teacher with66.66% in both categories increased to 81.25% with the category very well in the second cycle. So overall thereis an increase in activity of the teacher of 21.89%. At the student activity also increased in each cycle. In the firstcycle of an average percentage of 64.58% with the good category increased to 77.08% in the second cycle. Sooverall there is an increase in the activity of students 19.36%. Application of Learning strategies concept mapscan improve learning outcomes of students in class V SDN 58 Balai Makam.